2017
DOI: 10.1186/s12888-017-1372-5
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, psychiatric disorders and suicidal ideation in a National Representative Sample of active Canadian Forces members

Abstract: BackgroundPast research on the association between insomnia and suicidal ideation (SI) has produced mixed findings. The current study explored the relationship between insomnia, SI, and past-year mental health status among a large Canadian Forces (CF) sample.MethodData was obtained from the 2013 Canadian Forces Mental Health Survey (CFMHS), and included a large representative sample of Canadian Regular Forces personnel (N = 6700). A series of univariate logistic regressions were conducted to test individual as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…A growing body of research has shown that USA (US) military personnel are at elevated risk for insufficient sleep and poor sleep quality, with rates of sleep disturbance higher than rates in civilians (Klingaman, Brownlow, Boland, Mosti, & Gehrman, 2018;RAND Corporation;. These research findings are consistent with results of sleep study in Canadian and European military cohorts, although mixed results have also been reported (Danker-Hopfe et al, 2017;Pettersson, Saers, Lindberg, & Janson, 2016;Reijnen, Rademaker, Vermetten, & Geuze, 2015;Richardson, Thompson, & King et al, 2017). Based on a recent study that assessed pre-deployment psychosocial variables and insomnia complaints (defined as an Insomnia Severity Index ≥15; Morin, Belleville, Belanger, & Ivers, 2011) in soldiers located at Ft.…”
Section: Introductionmentioning
confidence: 69%
“…A growing body of research has shown that USA (US) military personnel are at elevated risk for insufficient sleep and poor sleep quality, with rates of sleep disturbance higher than rates in civilians (Klingaman, Brownlow, Boland, Mosti, & Gehrman, 2018;RAND Corporation;. These research findings are consistent with results of sleep study in Canadian and European military cohorts, although mixed results have also been reported (Danker-Hopfe et al, 2017;Pettersson, Saers, Lindberg, & Janson, 2016;Reijnen, Rademaker, Vermetten, & Geuze, 2015;Richardson, Thompson, & King et al, 2017). Based on a recent study that assessed pre-deployment psychosocial variables and insomnia complaints (defined as an Insomnia Severity Index ≥15; Morin, Belleville, Belanger, & Ivers, 2011) in soldiers located at Ft.…”
Section: Introductionmentioning
confidence: 69%
“…Numerous studies have indicated that insomnia is associated with suicidal ideation [ 13 16 ], suicide attempts [ 17 19 ], and death by suicide [ 20 22 ] among adolescents and adults. These studies laid the foundation for the relationship between insomnia and suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the relationship between insomnia and suicide is fully mediated by mental disorders [ 13 , 14 , 24 ]. Other studies have shown that insomnia remains an independent factor of suicidal ideation [ 15 , 16 ], suicide attempt [ 19 ], and death by suicide [ 21 , 22 ] after adjustments for mental disorders, substance abuse and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals in regional settings are vulnerable to a wide range of inequities of social circumstances, resource allocation, stigmatisation, and accessibility of healthcare [ 32 , 33 , 34 ], which could be implicated in this finding. Sleep disturbances is often used as a sensitive clinical marker of psychological distress, and has a dose-related relationship with developing and perpetuating late-life depression [ 35 ], as well as suicidal ideation [ 36 ]; and appears to be a moderate risk factor in this population. Life-time suicidal behaviours and late-life suicidal ideation are strongly predictive of late-life depression, as revealed clinically and in the literature [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%